Modelling and design of grid voltage oriented vector control scheme for DC railway recuperating system - Chuen Ling Toh; Chee Wei Tan (Institute of Advanced Engineering and Science, 2023)
The braking energy harvested by a railway vehicle can be restored to the utility grid with a power recuperating system. A grid connected voltage source inverter (VSI) is commonly used as a grid-feeding converter in the recuperating system. This paper proposes to integrate grid voltage oriented vector control (GVOVC) and third harmonic voltage injection pulse width modulation (THVI-PWM) technique for the VSI to ensure grid voltage and frequency synchronization. A simulation study is carried out to evaluate the feasibility of the proposed control and modulation schemes using MATLAB/Simulink. The results show that the proposed controller may reach steady-state operating mode within 7 ms by producing good quality AC voltages and currents waveforms. With the independent control of voltage quantities in dq reference frame, the regulation of active and reactive power could be realized.